Migration, Remittance and Poverty in Nepal - Gautam, Tika Ram (Economic Review of Nepal, 2019)
This paper aims to explore whether poverty rate vary by remittance receiving status (yes/no) households and to explain the association between remittance status (yes/no) and poverty status (poor/non-poor) of households across the provinces of Nepal. Based on third round of Nepal Living Standard Survey (NLSS) data the proportion of remittance receiving households and poverty rate is described. The association between remittance status and poverty status of households' is explained using chi-square test of independence. From Nepal about 56 percent households are receiving remittance. Based on the results this paper argues that the poverty rate widely varies; lowest in Bagmati (20.6%) to highest in Sudurpaschim (45.6%) province, across provinces. Similarly, the poverty rate also varies across remittance receiving households (21.5%) to remittance not receiving households (29.4%). The poverty rate is low in remittance receiving households compared to households not receiving remittance. However, the poverty rate in remittance receiving households across also varies across provinces ranging from 12.9 percent in province-1 to 45.1 percent in Sudurpaschim province. There is significant association [χ2-value=230074.923 is significant (p=0.000<α=0.01) at 0.01 level of significance] between the status of households based on remittance and poverty. The households receiving remittance are less likely (β=-1.283) to be poor compared to the household receiving no remittance.